Kolaborasi Matematika dan Bahasa Inggris dalam Peningkatan Kompetensi Literasi Siswa Madrasah Aliyah Swasta DDI Baru-Baru Tanga - Abdul Majid; Yonathan S Pasinggi; Usman, Usman; Yulia, Yulia; Rita Tuken (Yayasan Literasi Sains Indonesia, 2025)
This community service project aims to enhance the literacy competence of students at Madrasah Aliyah Swasta (MAS) DDI Baru-Baru Tanga through a collaborative approach integrating Mathematics and English subjects. The background of this program lies in the low level of students’ numeracy and foreign language literacy, which affects their analytical reasoning and scientific communication skills. The activity involved collaborative workshops for teachers, the development of bilingual contextual learning modules, and the implementation of project-based integrated lessons. The program was conducted over two months, engaging 60 eleventh-grade students and four subject teachers. The results indicated a significant improvement in students’ ability to read and interpret mathematical texts in English, analyze data, and present problem-solving results in an organized and communicative manner. Furthermore, students demonstrated a more positive attitude toward interactive and cross-disciplinary learning. This collaboration not only strengthened students’ literacy competence but also improved teachers’ pedagogical skills in implementing interdisciplinary learning models. The outcomes of this program highlight the importance of integrating subject collaboration as a strategic effort to promote literacy and foster a culture of innovation within Islamic educational institutions.